THE VISUALIZATION OF RELIGIOUS TOLERANCE INSIDE A PICTURE - Zulfi Zumala Dwi Andriani (2022)
Indonesian religious life has recently changed due to political issues that exploded after the general election held on April 17, 2019. This condition has disrupted the harmony of Indonesia's life and the raised intolerance among Indonesians. Along 2020, it was recorded some cases related the intolerance based on religion. Since the growing numbers of internet users among Indonesian people, it caused social media users in Indonesia has become a fertile ground for the spread of radical Islamic ideas and the increase of openness for piety in online spheres. Instagram is one of the currently popular social media among many people, especially young generations. Instagram was launched in October 2011 and immediately became viral for photo sharing. Infographics are one ways to visualize much complex information into one image uploaded on Instagram application. This paper will discuss infographics which was uploaded by @islamidotco account especially for visualizing the religious tolerance. The discourse analysis method by Teun Van Dijk was employed to analyse the infographics. This research is descriptive qualitative research, it is going to investigate how an infographic possibly became an alternative da’wa to visualize religious tolerance narratives on Instagram platform and how religious tolerance through infographics were constructed. The result reveals that @islamidotco account focussing on promoting religious tolerance by illustrating some infographics which visualize about respecting other religion, acknowledging diversity and supporting minorities. Pictures tell more accurate information than words, and thus, infographic can be an alternative technique for da’wah, especially in presenting moderate Islamic discourses among the propaganda of Islamic extremism discourses on social media especially in Instagram.